Legal Efforts Related to Legal Protection Againts Book Piracy Through Marketplace - Rizkina, Silfi; Suryono, Arief (International Journal of Educational Research & Social Sciences, 2024)
In Law No. 28 0f 2014 an Copyright it is confirmed that an act is considered copyright infringement if it violates the exclusive right of the creator to publish or reproduce and to grant permission or prohibit others who without his consent make, reproduce, or broadcast his copyrighted work.  The online marketplace is classified as an Electronic Trading System Operator. The research conducted uses normative legal research. The type of research used in this research is descriptive. The result of this research is that the Marketplace is responsible for prohibiting all sales and duplication of goods resulting from copyright infringement in the trading place it manages. Any marketplace manager is obliged to act in cracking down on novel piracy so as not to lose trust. If the marketplace is unable to overcome it, then it is time for repressive legal protection to take over to solve it.